Uncertainty and monetary policy experimentation: Empirical challenges and insights from academic literature - Matteo Cacciatore; Dmitry Matveev; Rodrigo Sekkel (Bank of Canada, 2022)
Central banks face considerable uncertainty when conducting monetary policy. Some of the reasons for this include limitations of economic data, the unobservability of key macroeconomic variables such as potential output, structural changes to the economy and disagreements over the correct model for the transmission of monetary policy. At the same time, monetary policy is affected by uncertainty from various sources, including lack of or imperfect observation of economic variables, structural economic changes and possible misspecifications using models. We draw from the academic literature to review some of the key sources of this uncertainty and their implications for the conduct of monetary policy. First, we discuss evidence on release lags and revisions to economic data. We also highlight uncertainty around measuring unobservable variables such as the output gap and the natural rate of unemployment. The strength of a trade-off between these measures of economic slack and inflation - a cornerstone of monetary policy - is itself subject to continuous reassessment. Second, the literature finds that different sources of uncertainty may make the optimal conduct of monetary policy either more or less responsive to economic shocks. Additionally, the benefits of tackling uncertainty by engaging in purposeful monetary policy experimentation are typically small but may become more significant during major structural change or following unprecedented shocks
Keywords: E3; E5; 330; Central bank research; Monetary policy and uncertainty; Potential output